Regulatory implementation of the occupational equivalent dose limit for the lens of the eye and underlying relevant efforts in Japan. (3rd April 2023) - Yokoyama, Sumi; Hamada, Nobuyuki; Tsujimura, Norio; Kunugita, Naoki; Nishida, Kazutaka; Ezaki, Iwao; Kato, Masahiro; Okubo, Hideki
Abstract: In April 2011, the International Commission on Radiological Protection recommended reducing the occupational equivalent dose limit for the lens. Such a new occupational lens dose limit has thus far been implemented in many countries, and there are extensive discussions toward its regulatory implementation in other countries. In Japan, discussions in the Japan Health Physics Society (JHPS) began in April 2013 and in Radiation Council in July 2017, and the new occupational lens dose limit was implemented into regulation in April 2021. To share our experience, we have published a series of papers summarizing situations in Japan: the first paper based on information available by early 2017, and the second paper by early 2019. This paper (our third paper of this series) aims to review updated information available by mid-2022, such as regarding regulatory implementation of the new occupational lens dose limit, recent discussions by relevant ministries based on the opinion from the council, establishment process of safety and health management systems, the JHPS guidelines on lens dose monitoring and radiation safety, voluntary countermeasures of the licensees, development of lens dose calibration method, and recent studies on exposure of the lens in nuclear workers and biological effect on the lens.